2014
DOI: 10.3923/pjbs.2014.248.253
|View full text |Cite
|
Sign up to set email alerts
|

Decolourization of Synthetic Textile Dyes using the Edible Mushroom Fungi Pleurotus

Abstract: The ability of three Pleurotus species (P. florida LCJ 65, P. ostreatus LCJ 183 and P. sajorcaju LCJ 184) was compared for the decolourization of bromophenol blue, brilliant green and methylred using by solid and liquid medium. All three Pleurotus species were effective in decolourizing the dyes on potato dextrose agar plate. During quantitative decolourization experiments, the absorption spectrum of the dye solution showed a steady decrease in decolourization with the increase in the days of incubation. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The decrease in lignin content of groundnut shell observed after 49 days of degradation by Pleurotus ostreatus, Lentinus squarrosulus and consortium of Pleurotus ostreatus and Lentinus squarrosulus showed that these mushrooms can remove lignin bonds that prevent holocellulose from being broken down to simple and fermentable sugar. This observation has been reported to be due to the production of lignindegrading enzymes by these organisms [23][24][25][26]. A similar observation of a decrease in lignin content of degraded groundnut shell by Pleurotus ostreatus for 5 weeks [17] and 30 days [18] has also been reported.…”
Section: Discussionsupporting
confidence: 69%
“…The decrease in lignin content of groundnut shell observed after 49 days of degradation by Pleurotus ostreatus, Lentinus squarrosulus and consortium of Pleurotus ostreatus and Lentinus squarrosulus showed that these mushrooms can remove lignin bonds that prevent holocellulose from being broken down to simple and fermentable sugar. This observation has been reported to be due to the production of lignindegrading enzymes by these organisms [23][24][25][26]. A similar observation of a decrease in lignin content of degraded groundnut shell by Pleurotus ostreatus for 5 weeks [17] and 30 days [18] has also been reported.…”
Section: Discussionsupporting
confidence: 69%
“…3). Similar results have been reported in literature in which three Pleurotus spp viz., P. florida, P. ostreatus P. sajor-cajuwere used to study their mycelial growth pattern and decolorized zone formation on PDA (Radhika et al, 2014). Similar results were also reported by Jebapriya and Gnanadoss (2013), for decolorization of bromophenol blue by P. florida and other white rot fungi.…”
Section: Effect Of Synthetic Dyes Concentration On Decolorization Efficiency Of Pleurotus Sppsupporting
confidence: 73%
“…500 ppm, 200 ppm and 100 ppm of each dyes viz. Bromophenol blue, Crystal violet, Methyl red, Methylene blue and Brilliant blue were poured into 90 mm Petri plates and allowed to solidify under Laminar cabinet (Radhika et al, 2014). The plates were inoculated with 5 mm mycelial disc from 7 days old pure culture and the positive control were used as unsupplemented Agar plates inoculated with respective culture and negative control were used as the un-inoculated plates supplemented with respective dye concentration under laminar air flow chamber and incubated at 25±2˚C.…”
Section: Qualitative Assaymentioning
confidence: 99%
“…Işık geçirgenliği ve gaz çözünürlüğü dengesi etkilendiğinden çözünmüş oksijen seviyesini azalmakta ve aerobik organizmalar için elverişsiz şartlar oluşmaktadır. Bu durum ise aneorobik süreci başlatarak su ekosistemini ciddi şekilde etkilemektedir [3], [4], [5].…”
Section: Introductionunclassified